Lodo de esgoto na recuperação de áreas degradadas: Efeito nas características físicas do solo - Sampaio, Thalita Fernanda [UNESP]; Guerrini, Iraê Amaral [UNESP]; Backes, Clarice [UNESP]; Heliodoro, Julia Carolina Athanázio [UNESP]; Ronchi, Helena Souza [UNESP]; Tanganelli, Kaliana Moro [UNESP]; de Carvalho, Nayara Cristina; Oliveira, Fernando Carvalho (My University, 2012)
The recovery of degraded areas is a slow process and requires the addition of organic residues to improve the soil physical properties. It is known that sewage sludge has a high content of organic matter and nutrients, acting as soil conditioner and supplying nutrients to soil and plants. In a degraded Entisol (typic Quartzipsamment) area, on the Fazenda Entre Rios of the company Suzano Bahia Sul Pulp and Paper, in Itatinga-SP, native Atlantic Forest species were planted. The area was treated with increasing doses of sewage sludge (0; 2.5; 5; 10; 15; and 20 t ha-1), which was compared with chemical fertilization and control (no sludge and no fertilizer). The objective was to evaluate the effects of sewage sludge on soil physical characteristics. The use of higher doses of sewage sludge increased aggregate formation and soil porosity, until 12 months after application. Soil humidity and porosity (macro, micro and total) increased until six months after application of the highest sewage sludge rate, whereas microporosity was influenced until 12 months after application.
Soil physical characteristics after the application of sewage sludge as soil conditioner
Keywords: Biosolids; Organic residues; Sandy soil